UTILIZATION OF GILLNET CATCHES FISHERMEN OF MATANG RAYEUK VILLAGE, NUSANTARA FISHERY PORT, EAST ACEH - Muhammad; Junaidi M. Affan; Rizwan; Razali; Wulan Agustri; Syamsul Rizal; Zulfan; Syarifuddin; Zulkarnain (Jurnal Pengabdian Bangsa, 2024)
The purpose of this community service is to determine the composition of the main and by-catch of gill nets and the size of the catch. This community service was carried out during April 2023 at PPN Idi Rayeuk, Matang Rayeuk Pedawa Puntong Village, East Aceh Regency. The data collection method used was obtained from primary data (surveys and interviews) which included the type, quantity, size, and weight of the gill net catch and secondary data can be obtained from scientific references books, journals, theses and dissertations). The data analysis used was the analysis of the composition of the catch and the analysis of the size of the catch. The results of the community service showed that the composition of the main catch of the gill net at a mesh size of 1¼ inches was tembang fish, at a mesh size of 2 inches was ribbon fish and at a mesh size of 3 inches was kapasan/kerot-kerot and kwee fish. By-catch with a net size of 1¼ inches is jackfruit seed fish (upeneus moluccensis), kurisi (nempiterus hexodon), petek (leiognathus equulus), yellow trevally (Atule mate), saurida (Saurida undosquamis), swanggi (Priacanthus hamrur), next (Psettodes erumei), parang-parang (chirocentrus dorab), tetengkek (megalaspis cordyla). ) and layur (trichiurus Sp.A). Next, at a mesh size of 2 inches, namely talang fish (scomberoides tala), diles (johnius carouna), petek (leiognathus equulus), moon (Megalops cyprinoides), machete (chirocentrus dorab), jackfruit (upeneus moluccensis), kurisi (nempiterus hexodon), kwee (carangoides armatus), tetengkek (megalaspis cordyla), gerot-gerot ( Pomadasys kaakan), kerong-kerong (Terapon Jarbua), and alu-alu (Sphyraena genie). Then at the 3 inch mesh size, namely the kapasan/kerot-kerot fish (Pomadasys argenteus), talang (scomberoides tala), petek (leiognathus equulus), kuro (Polydacctylus microstoma), diles (johnius carouna), parang-parang (chirocentrus dorab), mackerel (Scomberomorus Commerson), kapas (Gerres filamentosus), and tetengkek (megalaspis cordyla). The catch at the 1¼ and 2 inch mesh sizes is said to be not yet suitable for catching, while the 3 inch mesh size is said to be suitable for catching.